A study of local government strategies to promote youth entrepreneurial clusters in cultural and creative industries - Hung, Chi-Sen (Technium Business and Management, 2022)
2019 was the initial year of Taiwan regional revitalization; the Taiwanese government attempted to solve the issues of overpopulation in big cities due to urbanization, whereas the depopulation issues occur in the rural area. In 2015, the Taichung City Government launched the "Reaching-for-Stars Youth, Dream-Come-True in Taichung"(RSY project), which promotes the establishment of youth entrepreneurial clusters in Taichung City and invites young people of cultural and creative industries to return home for entrepreneurship. In order to investigate the Taichung City Government's strategy for promoting this project, this study adopted grounded theory, in-depth interviews, and field surveys. This study proposes the "Entrepreneurship Base Operation Strategy Framework", which contains five operational strategy facets, the government entrepreneurship policy, local entrepreneurship capital and environmental resources, operation management strategy for incubation and counseling, brand management and marketing of the entrepreneurship base, and local sustainable management.